อิทธิพลของ BA และระยะเวลาการให้อาหารในระบบไบโอรีแอคเตอร์แบบจมชั่วคราวต่อการเพิ่มจำนวนของต้นแก้วหน้าม้า - จันจุฬา ณัฐพงค์; พิมลรัตน์ พิมพรรณ (Thai Journal of Science and Technology, 2020)
Alocasia sanderiana Bull. is a unique plant with beautiful leaves. It grows under shade and even in the corner of various buildings. Its propagation is sucker division and seed propagation. Tissue culture is an effective technique, which can be used to multiply mass plantlet with shorter period of time. This research was divided into 2 experiments with completely randomized design. First experiment was to study effect of BA on micropropagation of A. sanderiana on agar medium. A. sanderiana were cultured on MS agar medium supplemented with various concentrations of BA (0, 1.0, 2.0, 3.0, 4.0, and 5.0 mg/L). The results showed that the highest shoot number (2 shoots) was obtained when 5 mg/L BA was used. Second experiment was to study duration time of feeding on A. sanderiana shoot induction in temporary immersion bioreactor. Small A. sanderiana shoots were fed with 200 mL of broth MS at different periods of time (2, 4, 6, and 8 minutes) twice a day in semi-automatic cultured system. The results showed that the highest shoot number (5.33 shoots) was obtained when 4 minutes of feeding was used.